Analysis of Adolescent Knowledge About Health Reproduction In The Working Area of The Youth Health Center Samarinda - Rahayu, Anik Puji; Shalsa Amalia Basir,; Dita Ranissa; Odhilia Jesica; Erina Nur Rahmad; Siti Rahma Ersha; Nur Asiyah Azhara (Fakultas Kedokteran, Universitas Mulawarman, 2024)
Introduction: Puberty is the period in which adolescent development, physical changes, and sexual maturity occur. Some teenagers undergo these changes at an earlier age than others. This can give rise to problems because adolescents' knowledge about reproductive health is still lacking. Purpose: The aim of this research is to know and understand teenagers’ knowledge about adolescent health reproduction in the Samarinda Youth Health Center working area. Methods: This is a type of quantitative descriptive research with a survey approach. The respondents in this study were teenagers aged 11-19 years, with as many as 30 respondents. Results: The research results showed that of the 30 respondents who were in the study, 17 respondents, or (57%), had a high level of knowledge about juvenile reproduction; 12 respondents, or (40%), had a medium level of knowledge; and 1 respondent, or (3%), had a lower level of knowledge about adolescent reproductive health. Conclusion: Based on the results of this research, it is necessary to provide health education to adolescents so that they increase their knowledge about adolescent reproduction and can maintain reproductive health and take the correct actions to maintain their reproductive health. This research conclusion must be health education with continuous that health reproduction to adolescent. Keyword : Knowledge, Reproductive Health, Adolescents